Superhydrophilicity of novel anodic alumina nanofibers films and their formation mechanism. (5th June 2017) - Peng, Rong; Yang, Wulin; Fu, Licai; Zhu, Jiajun; Li, Deyi; Zhou, Lingping
Abstract: A novel anodic alumina nanofibers structure, which is different from the traditional porous anodic structure, has been quickly fabricated via anodizing in a new electrolyte, pyrophosphoric acid. The effects of the solution concentration and the anodizing time on the formation of the anodic alumina nanofibers were analyzed. The results show that the nanostructure of anodic alumina can change to the nanofiber oxide from the porous oxide by increasing the solution concentration. Prolonging the anodizing time is beneficial to obtain alumina nanofibers at high solution concentration. Growth behavior of the alumina nanofibers was also discussed by scanning electron microscopy observations. Owing to the unique hexagonal structure of anodic alumina as well as the preferential chemical dissolution between the porous anodic alumina and the anodic alumina nanotips, the slightly soluble anodic alumina nanotips could form novel alumina nanofibers during anodizing. The results show that the nanofibers-covered aluminum surface exhibits superhydrophilic property, with a near-zero water contact angle. Such alumina nanofibers with superhydrophilic property could be used for various potential applications.